Konservasi Hutan Mangrove Serta Dampaknya Pada Masyarakat, Pantai Timur Kedonganan, Kabupaten Badung, Bali - Purba, An Hofen; Ranteallo, Ikma Citra; Kamajaya, Gede (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The mangrove forest conservation movement is a social movement that aims to save nature from the threat of destruction that is rampantly carried out by humans at this time. This research uses qualitative-descriptive research methods, and is expected to provide a complete picture of the conservation process and its importance for aspects of human life.Based on the results, the existence of mangrove forests on the East Coast of Kedonganan has a great impact on the socio-economic life of the surrounding community. With this forest, the income of the fishing community has increased, and this movement is certainly a forum for the community to increase kinship around the East Coast of Kedonganan. It can be concluded that the conservation carried out by the Segara Ayu Fishermen group has had a positive impact on the people of the East Coast of Kedonganan both in environmental and socio-economic terms.